Antarctica : a biography - Day, David, 1949- (Oxford University Press, 2013)
For centuries it was suspected that there must be an undiscovered continent in the southern hemisphere. But explorers failed to find one. On his second voyage to the Pacific, Captain Cook sailed further south than any of his rivals but still failed to sight land. It was not until 1820 that the continent's frozen coast was finally sighted. Territorial rivalry intensified in the 1840s when British, American, and French expeditions sailed south to chart further portions of the continent that had come to be called Antarctica.